2007
DOI: 10.1126/science.1142979
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Optical Spectroscopy of a Strongly Driven Quantum Dot

Abstract: Quantum dots are typically formed from large groupings of atoms and thus may be expected to have appreciable many-body behavior under intense optical excitation. Nonetheless, they are known to exhibit discrete energy levels due to quantum confinement effects. We show that, like single-atom or single-molecule two- and three-level quantum systems, single semiconductor quantum dots can also exhibit interference phenomena when driven simultaneously by two optical fields. Probe absorption spectra are obtained that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
269
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 352 publications
(289 citation statements)
references
References 28 publications
14
269
0
3
Order By: Relevance
“…The full width at half maximum (FWHM) of the resonance is about 0.7 GHz. Although in four-wave mixing studies the zero-phonon linewidth has been shown to be limited by radiative decay to about 170 MHz 12,13 , PL linewidths and/or resonantly measured single QD excitation linewidths are usually found to lie in the range of 500 MHz to several GHz [5][6][7][8][9][10][11]17,[19][20][21] . The additional "apparent" broadening is due to spectral diffusion, a process by which the QD transition frequency is randomly shifted during the measurement 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The full width at half maximum (FWHM) of the resonance is about 0.7 GHz. Although in four-wave mixing studies the zero-phonon linewidth has been shown to be limited by radiative decay to about 170 MHz 12,13 , PL linewidths and/or resonantly measured single QD excitation linewidths are usually found to lie in the range of 500 MHz to several GHz [5][6][7][8][9][10][11]17,[19][20][21] . The additional "apparent" broadening is due to spectral diffusion, a process by which the QD transition frequency is randomly shifted during the measurement 17 .…”
mentioning
confidence: 99%
“…(2) with s/2π=0.7 GHz, chosen to coincide with the measured excitation linewidth of Fig. 1(c) which is also typical for InAs QDs [5][6][7][8][9][10][11]17,[19][20][21]23 . In comparison, Fig.…”
mentioning
confidence: 99%
“…When d Ω is strong, it will dress the spin ground state X − and the trion state T − . In the case where d Ω is larger than the trion transition linewidth, the absorption spectrum of the probe beam will split into two peaks when scanning across transition , which are known as Autler-Townes (AT) doublets [20], and has been demonstrated in a neutral QD [21,22]. The spectral features of the probe absorption spectrum in our experiment is a combination of the AT splitting and the CPT quantum interference effect [7], where the spectral positions of the side bands can be determined by the AT splitting and the central feature in the absorption spectrum is due to the CPT effect, not a simple summation of the tails of the AT Lorentzian lineshapes.…”
mentioning
confidence: 99%
“…Time-resolved Rabi oscillations have also been observed experimentally for a QD placed in a microcavity where the lightmatter interaction was in the strong coupling regime. Here, the Rabi oscillations reveal themselves in the time-resolved correlation function [140,141,142]. Recently time-resolved Rabi oscillations have been measured by monitoring the time-dependent resonance fluorescence from a singly charged QD, where a TLS is formed by the negatively charged ground state and the trion state [143].…”
Section: Rabi Oscillationsmentioning
confidence: 99%